China’s urban-rural expansion and natural habitat loss since the 1980s: Retrospective analysis and future suggestions - Han, Lijian; Zhang, Lumiao; Zhou, Weiqi; Li, Weifeng; Qian, Yuguo (Frontiers in Environmental Science, 2022)
Natural habitats transformed to city or countryside with human activities of different intensities have reshaped regional and global landscapes, especially in those rapid developed low- and mid-income countries, like China. China’s rapid shift in urban and rural expansion, which are greater than and equal to, and below county-level’s artificial land expansion, and reduction in farmland and ecological land are important for determining future urban and rural development under the conservation and protection of farmland and ecosystems; however, such an understanding is still inadequate. Here, we show that both urban and rural expansions have encroached on farmland and ecological land since 1980; rural areas, with 1.33 km2 × 105 km2 in 2020, remain larger than urban areas, with 0.97 km2 × 105 km2 in 2020. However, urban areas (1857.5 km2/year) increased faster than rural areas (695.0 km2/year) during 1980–2020, rural expansion primarily occurred in the 1980s and 1990s, and urban expansion primarily occurred after 2000 especially 2000s. Farmland is the major land cover that has been occupied by urban and rural expansion for 53.7 and 39.1 thousand km2, especially in East China’s densely populated areas. And, both farmland and ecological land were primarily encroached during 2000s. Our results demonstrate imbalanced urban and rural expansion and encroachment on farmland and ecological land; thus, both forms of encroachment should be optimized at the regional scale based on the socioeconomic needs and natural conditions, and diverse policies can be designed to support local sustainable development.